Second honeymoon [compact disc, unabridged] - Patterson, James, 1947-; Roughan, Howard (Hachette Audio, 2013)
A newlywed couple steps into the sauna in their deluxe honeymoon suite, and never steps out again. FBI Agent John O'Hara is deep into solving the case, while Special Agent Sarah Brubaker is hunting another ingenious serial killer, whose victims all have one chilling thing in common.